2002
DOI: 10.1016/s0022-5347(05)65416-x
|View full text |Cite
|
Sign up to set email alerts
|

Pain and Morbidity of an Extensive Prostate 10-Biopsy Protocol: A Prospective Study in 289 Patients

Abstract: Although minor complications are common, the extensive 10-core prostate biopsy protocol is associated with few major complications. The occurrence and intensity of pain and discomfort are in the range reported after the standard 6-core biopsy protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
50
3
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 13 publications
7
50
3
5
Order By: Relevance
“…The scale has also been used in visually impaired patients and to evaluate pain intensity after surgery (12,13). A study assessing pain intensity after TRUS-GB reported a mean NRS score of 3.2 (9). This is consistent with our findings, while pain intensity for MRI-GB was lower.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The scale has also been used in visually impaired patients and to evaluate pain intensity after surgery (12,13). A study assessing pain intensity after TRUS-GB reported a mean NRS score of 3.2 (9). This is consistent with our findings, while pain intensity for MRI-GB was lower.…”
Section: Discussionsupporting
confidence: 91%
“…In the literature the rate of hematuria after TRUS-GB is in the range of 11%-57%, while a higher rate (79%) of mostly mild hematuria was observed in our patient cohort (8,9,14).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…[8] Hematuria is the most frequently seen complication following TRUS-guided prostate biopsy.Hematuria with an incidence ranging between 14.4, and 84%, persists for an average of 2.7-5.1 days which can extend up to 20 days. [5,7,[9][10][11][12][13][14][15][16][17][18][19][20][21] As a minor complication, hematuria which is frequently encountered after biopsy, generally lasts briefly without any need for additional treatment However, in 0.25-0.7% of the cases hematuria leading to clot retention and/or requiring transfusion can be seen. [5,13] Hematospermia which is another frequently seen complication has been reported in 5.7, and 89% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, increasing the number of biopsies does not seem to add to pain and anxiety from the procedure. 15 In this study, all patients underwent a standard six-sector biopsy.…”
Section: Relevance Of Study To Biopsy Protocolsmentioning
confidence: 99%